Renegade M.D. : a doctor's stories from the streets - Partovi, Susan (Renegade Press, 2023)
"Dr. Susan Partovi first experienced poverty medicine volunteering at a dump site in Tijuana during high school. There, she recognized the need for all people to have access to quality medical care. Over the years, she has worked in various facilities around Los Angeles County, incorporating her renegade method of going the extra mile for her patients. As Medical Director of Homeless Health Care Los Angeles, she works to provide a safety net of care for the underserved skid row community and surrounding neighborhoods."--Amazon.com.